Epiphyte Identification on Kappaphycus alvarezii Seaweed Farming Area in Arungkeke Waters, Jeneponto and The Effect on Carrageenan Quality - Sri Redjeki Hesti Mulyaningrum; Hidayat Suryanto Suwoyo; Mudian Paena; Bunga Rante Tampangallo (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
Kappaphycus alvarezii which is widely cultivated at sea is susceptible to other algae that drift away and attach as epiphyte. This study aims to identify epiphyte on seaweed farming K. alvarezii and its effect on carrageenan quality. The study was conducted on K. alvarezii seaweed farming area in Jeneponto, South Sulawesi. Sample of epiphyte was obtained from four stations. Epiphyte was identified in laboratory based on its morphological characteristics and calculated its density. Carrageenan yield and gel strength of healthy seaweed and those infected one were analyzed in laboratory in triplicates for each sample. Data were statistically analyzed using independent samples t-test analysis. Present study showed that there were 6 epiphytes species on the seaweed farming area, namely: Entheromorpha intestinalis, Ceramium sp., Neosiphonia apiculata, Chaetomorpha crassa, Hypnea sp., and Gracilaria sp. The average of epiphytic density in cultivation area was (24.26±9.64)%. Healthy seaweed and infected one had significantly different carrageenan yield and gel strength (P<0.05). Healthy seaweed had higher carrageenan yield (48.17±1.62)% and gel strength (1130.76±8.42) g cm-² than infected seaweed which had carrageenan yield (42.47±0.23)% and gel strength (958.22±10.85) g cm-².